Bahasa Gaul di Media Sosial WhatsApp Ditinjau dari Wujud dan Makna: Penelitian - Ainaya Sukma Pitaloka; Ahmad Rifai; Hadi Riwayati Utami (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of communication technology has influenced the way teenagers interact, especially through social media platforms like WhatsApp. This study aims to describe the forms and meanings of slang used in teenagers' communication on WhatsApp. This study used a qualitative descriptive approach, using data in the form of WhatsApp message transcripts collected in June 2025. The results indicate that the forms of slang used include abbreviations, registers, puns, foreign languages, swear words, non-standard words, non-compliance with spelling principles, and acronyms. Slang is used to expedite communication, create intimacy, and convey a modern and expressive impression.